Study on carrying capacity and energy absorption characteristics of curved sandwich beam negative stiffness structure - JIANG Wei; REN Lianling; LIU Yanqi; SONG Chunfang; LU Chunyan (Jixie qiangdu)
In order to improve the carrying capacity of double curved beams negative stiffness structure composed of two curved beams arranged in parallel, the curved sandwich beam negative stiffness structure was proposed. The design idea was to array the sandwich straight beam between the upper and lower curved beams of the double curved beam negative stiffness structure, and the bearing capacity and energy absorption characteristics were studied systematically. Firstly, the negative stiffness structure model was fabricated using 3D printing technology and silicone emolding process, the compressive mechanical response of the curved sandwich beam and double curved beam negative stiffness structure was compared and analyzed by quasi-static compression experiment, and the reliability of the finite element simulation model was verified. Then, the influence of structural parameters (width, spacing, height and angle) of the sandwich straight beam on the bearing capacity and energy absorption characteristics of the negative stiffness structure was studied by simulation. The results indicate that the introduction of the sandwich significantly enhances the load-bearing capacity of the double curved beam negative stiffness structure. Compared with the spacing and angle of the sandwich straight beam, increasing the width and height of the sandwich straight beams can notably enhance the load-bearing capacity and energy absorption capacity of the structure.